The ethics of biobanking: Assessing the right to control problem for broad consent. (22nd January 2019) - Manson, Neil C.
Abstract: The biobank consent debate is one with deeply held convictions on both the 'broad' and 'specific' side with little sign of resolution. Recently, Thomas Ploug and Soren Holm have developed an alternative to both specific and broad consent: a meta‐consent framework. The aim here is to consider whether meta‐consent provides a 'solution' to the biobank consent debate. We clarify what 'meta‐consent' actually is (arguing that the label is a misnomer and 'consent à la carte' is more accurate). We identify problems with Ploug and Holm's arguments, and some challenges for meta‐consent. We focus on whether there is any ethical obligation to provide consent à la carte. There may seem to be so, especially if we draw upon an unclear appeal to the ethical significance of 'respect for autonomy'. Similarly, there might seem to be an intuitive inference from the fact that ethically legitimate research requires informed consent to the conclusion that it thereby requires consent à la carte. It is shown that this line of inference is mistaken.